A implantação da avaliação em saúde da atenção básica na perspectiva das equipes de ESF - Mayer, Bárbara Letícia Dudel (2014)
It is a qualitative, exploratory-descriptive research, which aims to identify how the professionals of the Family Health Strategy of the Health Region Green Fields of the 4th Regional Health of Rio Grande South, participate in the implementation of the National Programme for Improving Access and Quality in Primary Care. The research was conducted with two teams of two municipalities located in the central region of the state and who performed "well above average" in the first evaluation of Programme after his accession in 2011. The data collection comprised technique of Focus Group, where two sessions were held with each team, plus the application of instrument sociodemographic and individual assessment questionnaire own research. Occurred in the period from January to March 2014. Data analysis was through the use of Atlas Ti Software and Content Analysis proposed by Bardin, as well as sociodemographic data were descriptive statistical treatment. The theoretical framework of this research includes the History of Dialectical Materialism. This study meets the ethical issues in research pursuant to Resolution nº466 of December 12, 2012 of the National Health Council. Of the 33 study participants, 21 were in town A and 12 in B, the feminization of these teams came with the literature, as well as the extension of the minimum teams to extended teams, plus the average age of 42 years, with university degree. Work on average 10 years in the area of Public Health and there are 6 in the current Basic Health Unit. Among the 33 subjects, 29 had never worked in another Family Health Strategy, the means of ingress was by the tender. Workers identify adherence to National Programme initially promoted the detachment of the working process which allowed visualization of the same and identify gaps for the development of actions; gave support to the teams for the implementation and/or changes in actions primarily to the consolidation of team meetings; management of daily increased to a collective production; work was organized and systematized. We conclude that the evaluation has provided the qualification of primary care however is still not evident appreciation of these workers and the need for proposals focused on issues such as Matrix Support so that they can be heard, valued and have spaces for discussion, reflection and learning.